Spiral methodology of the software life cycle oriented to the advertising service applying ISO 12207 - Ogosi Auqui, José Antonio (2021)
The purpose of this work is to study the application of spiral methodology that advertising entities may use today, applying ISO 12207, obtaining as a result information from some institutions that already promote the use of this methodology, as well as the possibilities of implementation in institutions that have been stranded with regard to technological modernization in their institutions.